1 + 1 >> 2: Dramatically Enhancing the Emission Efficiency of TPE‐Based AIEgens but Keeping their Emission Color through Tailored Alkyl Linkages. (21st February 2018) - Dang, Dongfeng; Qiu, Zijie; Han, Ting; Liu, Yong; Chen, Ming; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract: Currently, the development of aggregation‐induced emission (AIE) luminogens (AIEgens) has enabled us to "see" never before seen scenery. However, not all AIEgens exhibit the impressive emission efficiency in aggregated states. Moreover, the emission color of AIEgens can be seriously affected when their performance is improved. Therefore, to overcome this limitation, an efficient method is proposed here through the tailored alkyl linkages to greatly improve the emission efficiency of tetraphenylethene (TPE)‐based AIEgens but retain their emission color. Encouragingly, significantly enhanced emission efficiency is achieved with the quantum yield up to 68.19% and 65.20% for BTPE‐C4 and BTPE‐C8, respectively, in contrast to that of TPE (25.32%), demonstrating the proverb that one plus one is much larger than two (1 + 1 >> 2). Interestingly, when alkyl linkages in skeletons are fine‐tuned, self‐assembled nanorods, nanosheets, and nanofibers are successfully achieved for BTPE‐C1, BTPE‐C4, and BTPE‐C8 in tetrahydrofuran and water system. Also, these developed emissive AIEgens not only exhibit impressive response to the environmental stimuli of mechanical force, viscosity, temperature, and light, but can also be used to dynamically monitor and control the phase‐separated morphology in polymeric blends. Abstract : To enhance the emission efficiency of tetraphenylethene‐based aggregation‐induced emission (AIE) luminogens (AIEgens) but retain their emission color, a facile strategy through the tailored alkyl linkages is proposed. All these developed AIEgens here exhibit impressive response to the stimuli of mechanical force, viscosity, temperature, and light, which can also be used to monitor and control the phase‐separated morphology in polymeric blends.